Examining The Influences Of Governance And Economic Development Level On Happiness:Case Of High Income Asia And Europe - Hui, Cathrine Chan Bao; Muhammad Asraf, Abdullah; Kueh, Jerome; Audrey, Liwan; Rosita, Hamdan (2016)
This study examines the association between governance and human development index with happiness using panel data fixed effect and random effect estimation approach. The findings from the study stresses the importance of good governance in influencing the increase in life satisfaction. It can be interpreted that good governance stimulates happiness in a positive manner. It is worth mentioning that good governance is crucial if the objective of the government is to raise life satisfaction of its citizens. The government in developed Asia and Europe can increase happiness and promote inequality through enhancement in the quality of governance. This can be done by ensuring good practices in managing the economy and resources of the country. However, the relationship between human Development Index as a proxy for socio-economic achievement and happiness is inconclusive and not significant. This finding is not as expected because past studies have supported the significance of health and social connectedness on happiness for example Easterlin (2003). Nevertheless, control variables such as inflation and unemployment show negative associations with happiness which are in line with past literature for example Clark and Oswald (1994); Winkelmann and Winkelmann (I998); and Agan, Sevinc and Orhan (2009).